2017
DOI: 10.1007/s12011-017-1095-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Inorganic Vanadium on Growth Performance, Endocrine Variables and Biomarkers of Bone Health in Crossbred Calves

Abstract: The nutritional essentialities of transition element vanadium (V) as micro-nutrient in farm animals have not yet been established, though in rat model, vanadium as vanadate has been reported to exert insulin-mimetic effect and shown to be needed for proper development of bones. The objective of this study was to determine the effect of V supplementation on growth performance, plasma hormones and bone health status in calves. Twenty-four crossbred calves (body weight 72.83 ± 2.5 kg; age 3-9 months) were blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…In the present study ADG and feed efficiency were not significantly influenced by inorganic vanadium supplementation. Similar to our findings (Pal et al 2017) reported that supplementation of crossbred calves with inorganic source of vanadium (upto 9 ppm) did not change the dry matter intake, growth performance and feed efficiency. Similarly, Heidari et al (2016) reported that dietary supplementation of 0.04, 0.08 and 0.12 mg of V as vanadyl sulfate per kg metabolic body weight did not affect body weight, body condition score, dry matter intake and energy balance in multiparous periparturient Holstein cows.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study ADG and feed efficiency were not significantly influenced by inorganic vanadium supplementation. Similar to our findings (Pal et al 2017) reported that supplementation of crossbred calves with inorganic source of vanadium (upto 9 ppm) did not change the dry matter intake, growth performance and feed efficiency. Similarly, Heidari et al (2016) reported that dietary supplementation of 0.04, 0.08 and 0.12 mg of V as vanadyl sulfate per kg metabolic body weight did not affect body weight, body condition score, dry matter intake and energy balance in multiparous periparturient Holstein cows.…”
Section: Resultssupporting
confidence: 92%
“…Homogeneous to our findings Heidari et al (2016) reported that supplementation of vanadium at different levels during a transition period, incremented in plasma glucose level and decremented the insulin: glucose ratio quadratically. However, the findings on blood glucose levels in ruminants have been inconsistent upon vanadium among studies; plasma glucose remained unaffected (Pal et al, 2017); increased (Heidari et al 2016), or decreased (Pederson et al, 1989;Zarqami et al, 2018). This might be because of vanadium influences the expression of GLUT4 protein or sensitivity of insulin may vary among species or difference in dosage.…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited information is available on the role of dietary V on performance especially in farm animals. In a recent study, dietary supplementation of 0, 3, 6 or 9 mg inorganic V/kg DM did not alter growth performance and feed efficiency in Crossbred Calves (Pal, Mani, Tripathi, Kumar, & Kewalramani, ).…”
Section: Discussionmentioning
confidence: 92%
“…The Ce group consists of the elements La, Ce, Pr, Nd, Pm, Sm, and Eu, whereas Y group comprises the elements Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y [11]. The importance of various inorganic elements (commonly known as minerals) in human, animal and plant nutrition are very familiar and are required for various metabolic functions [12][13][14]. Now, among inorganic elements, REE emerges as new generation growth promoter feed additive alternative to feed antibiotics for livestock.…”
Section: Introductionmentioning
confidence: 99%